Private Durchsetzung von Lieferkettenregulierung: Eine Analyse im Kontext des europäischen Wirtschaftsrechts - Längle, Jan (Nomos Verlagsgesellschaft mbH & Co. KG, 2026)
Using the Corporate Sustainability Due Diligence Directive (CSDDD) as an example, the study examines how corporate conduct in a globalized economy can be effectively regulated and whether civil liability is necessary to ensure meaningful enforcement. To address these questions, the study employs a triad of methods combining intradisciplinary, economic, and comparative-law perspectives, drawing on various areas of European economic law as well as U.S. law. Its aim is to develop a de lege ferenda reform proposal.